Виявлення ризиків в інноваційних програмах розвитку металургійного підприємства - Швець, Є. С.; Рулікова, Н. С. (НТУ "ХПІ", 2015)
Розглянуто теоретичні аспекти управління ризиками в інноваційних програмах розвитку металургійного підприємства, їх класифікація по основних ознаках, а також етапи процесу управління ризиками та методи управління ризиками в інноваційних програмах розвитку металургійних підприємств за сучасних умов розвитку України.

The theoretical aspects of risk management in innovative programs of metallurgical enterprises, their classification on the basic signs and stages of the risk management process and methods of risk management in innovative programs of metallurgical enterprises in modern conditions of Ukraine are considered. Conclusions were made about the essential things that are important especially for risks arising in the company due innovative development selecting.
Risks identifying in innovation development programs of metallurgical enterprises
Keywords: металургійна галузь; управління ризиками; інноваційні ризики; ризик-орієнтований підхід; risk-based approach; innovative program development; external and internal risks